1990
DOI: 10.1002/ajh.2830340403
|View full text |Cite
|
Sign up to set email alerts
|

Infant leukemia: An analysis of nine chinese patients

Abstract: A study was made of the cellular and molecular characteristics of nine Chinese infants, consecutively presenting with acute leukemia. Five cases were acute lymphoblastic leukemia (ALL); four were acute nonlymphoblastic leukemia (ANLL). Hyperleukocytosis, hepatosplenomegaly, and poor response to conventional therapy were common features, and CNS involvement was detected at diagnosis in three cases. The blast cells from all five cases with ALL expressed early B-cell markers, i.e., HLA-DR+, CD19+, but CD10-. Term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The frequency of this family of translocations affecting chromosome band llq23 has been estimated to be approximately 5% in adult and childhood acute leukaemias (Abe and Sandberg, 1984;Raimondi et al, 1989). By contrast, the incidence of llq23 abnormalities in leukaemias in infants of under 12 months of age has been found to be much higher (75% or greater) (Abe et al, 1983;Kaneko et al, 1988Chuu et al, 1990Gibbons et al, 1990). In addition to such findings in "de novo" leukaemias, evidence is emerging to link epipodophyllotoxin treatment of malignant disorders to the occurrence of secondary leukaemias with llq23 abnormalities (Pui et al, 1989;Prieto et al, 1990;Pedersen-Bjergaard and Philip, 1991;Whitlock et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of this family of translocations affecting chromosome band llq23 has been estimated to be approximately 5% in adult and childhood acute leukaemias (Abe and Sandberg, 1984;Raimondi et al, 1989). By contrast, the incidence of llq23 abnormalities in leukaemias in infants of under 12 months of age has been found to be much higher (75% or greater) (Abe et al, 1983;Kaneko et al, 1988Chuu et al, 1990Gibbons et al, 1990). In addition to such findings in "de novo" leukaemias, evidence is emerging to link epipodophyllotoxin treatment of malignant disorders to the occurrence of secondary leukaemias with llq23 abnormalities (Pui et al, 1989;Prieto et al, 1990;Pedersen-Bjergaard and Philip, 1991;Whitlock et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Immunophenotypic studies were performed by previously described methods. 10 Standard-risk ALL was defined by the following criteria: (1) leukocyte count Ͻ10 × 10 9 /l for patients aged 1 to 2 years or 7 to 10 years; Ͻ50 × 10 9 /l for those aged 2 to 7 years; and (2) non-T, non-B immunophenotype, no central nervous system (CNS) leukemia, as defined by the presence of any leukemic lymphoblasts identified on cytocentrifuged smears of cerebrospinal fluid, 11 or the presence of cranial nerve palsies and the lack of expression of two or more myeloid-associated antigens (CD11, CD13, CD14, CD15 or CD33).…”
Section: Diagnosismentioning
confidence: 99%
“…These rearrangements are observed in acute leukemias, especially-t(4;11), t(1;11), and t(11;19) translocations (2,3) in acute lymphoid leukemias (ALL) and t(1;11), t(2;11), t(6;11), t(9;11), t(10;11), t(l1;l17), and t(X;ll) in acute myeloid leukemias (AML) (4)(5)(6)(7)(8). The frequency of translocations involving this region is notably higher in infants (estimated to be 75%) (9)(10)(11) than in children and adults (=5%) (12,13). It has been shown that this region of the genome contains the human trithorax-like gene 1 (Htrxl gene), which is interrupted in the translocation event in infant leukemic patients and in the cell line RS4;11 (14).…”
mentioning
confidence: 92%